Nurses’ Performance Assessment Based On Nursing Clinical Authority: A Qualitative Descriptive Study - Supri, Aisyah; Rachmawaty, Rini; Syahrul, Syahrul (Journal Of Nursing Practice, 2019)
Background: One of nursing management functions is organizing nursing staff through assessing their working performances. Managing nursing staff in order to improve their working performance is vital. Thus, it needs to be well-designed to meet the patients’ expectation on health care quality. Nurses’ performance is defined as the action, achievement, or fulfillment of nurses’ responsibilities based on their tasks that have been assigned to them. Purpose: The aim of this study was to describe the nurses’ performance assessment and the nurse activities based on nursing clinical authority at the Dr. Wahidin Sudirohusodo hospital Makassar. Methods: This research is a qualitative descriptive study. Data were gathered from Focus Group Discussion (FGD), individual interviews, and document analysis. Results: The study results showed that generally the assessment of the nurses’ performances at the Dr. Wahidin Sudirohusodo hospital has been conducted since 2015. However, there were still some areas that need to be improved, such as the quantity indicator assessment that is currently not developed based on the nursing clinical authority. In fact, the assessment of nurses' performance for quantity indicators should be adjusted to the nursing clinical authority that has been assigned to them after completing the credentialing process as stated in the Nurse Clinical Assignment Letter. Conclusion: The assessment of nurses’ performance should be adhered to the nursing clinical authority and it is better if hospital managers may synchronize the nursing clinical authority with the online nursing logbook provided in the Hospital Information System